Corporate social responsibility, perceptions and practices of businessmen in selected small and medium enterprises in Iloilo City - Rebueno, Mary Rose G.; Elizaga, Maria Elena M. (Danyag :the UPV journal of humanities and social sciences, 2007)
"This paper presents the CSR perceptions and practices of businessmen in selected small and medium enterprises in Iloilo City. It describes the businessmen's understanding of CSR, the drivers of socially responsible behavior, perceptions of business benefits from the practice of CSR, and structured arrangements for CSR. The paper also explores possible roles that government could play in promoting more socially responsible behavior in the business community. Furthermore, it examines problems in CSR involvements, and recommends appropriate measures to enhance CSR practices of Iloilo businessmen."